Faktor-faktor yang Berkontribusi Terhadap Problematic Internet Use (PIU) Pada Siswa: Sebuah Systematic Literature Review - 'Aliyah, Shabrina Muyassirotul; Rahman, Diniy Hidayatur; Indreswari, Henny (Universitas Muhammadiyah Metro, 2023)
Internet and gadget collaboration provides various conveniences for teenagers to find information and communicate through various available applications, thus triggering their interest in continuing to access the internet. But on the other hand, the use of the internet can cause the phenomenon of Problematic Internet Use (PIU) in students. PIU is defined as an inability to control internet use which leads to various negative consequences. PIU Relating to student development tasks in the aspect of Personal Development. Optimizing the objectives of the youth development mandate in the aspect of Personal Development can be carried out through the provision of Guidance and Counseling services, both in the form of preventive and curative services. To support these efforts, this study aims to identify factors that contribute to PIU. The research method used is Systematic Literature Review (SLR). By applying the PRISMA method, research was conducted on scientific articles published in 2013-2023. From the data collection process, 23 articles were obtained that were relevant to the research question from Science Direct, Springer Link, Elsevier, Sage Journals, Wiley Online Library, Taylor and Francis Group, Google Schoolar, Research Gate, APA PsycNet, and PubMed. The results of the research show that the factors that contribute to Problematic Internet Use (PIU) in students consist of personal factors and social factors. These factors can contribute positively or negatively to Problematic Internet Use (PIU) in students.